Polyimides based on aromatic diisocyanates containing pendent flexible alkoxy chains and aromatic dianhydrides: synthesis, characterization, and liquid-crystal alignment properties - Sarkar, Anjana; Halhalli, Mahadeo R.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2009)
Four new aromatic diisocyanates containing pendent flexible alkoxy chains, namely, 5-butyloxy-1,3-phenylenediisocyanate, 5-octyloxy-1,3-phenylenediisocyanate, 5-dodecyloxy-1,3-phenylenediisocyanate, and 5-hexadecyloxy-1,3-phenylenediisocyanate, were synthesized by Curtius rearrangement of the corresponding 5-alkoxy-1,3-phenylene diacylazides. These diisocyanates were each polycondensed with three commercially available aromatic dianhydrides: 4,4'-oxydiphthalic anhydride, 3,3',4,4'-(hexafluoroisopropylidene) diphthalic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride-in benzonitrile in the presence of 1,4-dizabicyclo[2.2.2]octane as a catalyst to obtain a series of polyimides with inherent viscosities in the range 0.16-0.43 dL/g. Except for 3,3',4, 4'-benzophenonetetracarboxylic dianhydride based polyimides, all of the polyimides were found to be soluble in dichloromethane, m-cresol, 1-methyl-2-pyrrolidinone, tetra-chloroethane, and pyridine either at room temperature or on heating and could be cast into tough, flexible, transparent films from a solution in in-cresol or tetra chloroethane. X-ray diffractograms revealed that the polyimides with longer alkoxy chains had layered structures. The glass-transition temperature of the polyimides containing pendent flexible alkoxy chains were in the range 159-246 degrees C as measured by differential scanning calorimetry. The temperature for the 10% weight loss of the polyimides was in the range 410-460 degrees C in a nitrogen atmosphere, which indicated good thermal stability. A pretilt angle of 2.97 degrees was observed for the polyimide derived from 5-octyloxy-1,, 3-phenylenediisocyanate and 4,4'-oxydiphthalic anhydride. (c) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 461-472, 2009
Keywords: High performance polymers; polyimides; Thermal properties

Cyanate ester resins containing pentadecyl-substituted cyclohexyl moiety: synthesis, curing and structure-property relationship - Kulkarni, Arun D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
Cyanate ester (CE) monomers containing pentadecyl-substituted cyclohexyl moieties such as 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane and 1,1-bis(4-cyanatophenyl) cyclohexane were synthesized and characterized by Fourier transform infrared, proton-nuclear magnetic resonance (H-1-NMR) and carbon-nuclear magnetic resonance (C-13-NMR) spectroscopies as well as differential scanning calorimetry (DSC). Both 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane and 1,1-bis(4-cyanatophenyl) cyclohexane exhibited better processability coupled with lower melting points, lower cure onset with broad cure exotherm than the commercially available CE monomer, namely, 2,2-bis(4-cyanatophenyl) propane. Glass transition temperatures of cured 2,2-bis(4-cyanatophenyl) propane, 1,1-bis(4-cyanatophenyl) cyclohexane and 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane were observed to be 288 degrees C, 302 degrees C and 160 degrees C, respectively. Cured 1,1-bis(4-cyanatophenyl) cyclohexane displayed higher storage modulus (1.59 x 10(9) Pa) than 1,1-bis(4-cyanatophenyl) 3-pentadecylcyclohexane (1.07 x 10(9) Pa) and 2,2-bis(4-cyanatophenyl) propane (1.39 x 10(9) Pa). The order of thermal stability of cured polycyanurates was found to be 2,2-bis(4-cyanatophenyl) propane > 1,1-bis(4-cyanatophenyl) cyclohexane > 1,1-bis(4-cyanato phenyl) 3-pentadecylcyclohexane. The moisture absorption of cured resins derived from 1,1-bis(4-cyanatophenyl) 3-pentadecyl cyclohexane and 1,1-bis(4-cynatophenyl) cyclohexane was found to be lower than that of 2,2-bis(4-cynatophenyl) propane implying the role of pentadecyl substituent and/or cyclohexyl moiety in imparting hydrophobicity to the polycyanurates.
Keywords: (pentadecyl substituted) cyclohexyl; curing; cyanate ester resin; thermosets

Synthesis and characterization of polyetherimides containing multiple ether linkages and pendent pentadecyl chains - Tawade, Bhausaheb V.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Polymer International, 2015)
4-(4-(4-(4-Aminophenoxy)-2-pentadecylphenoxy)phenoxy)aniline (APPPA) was synthesized starting from cashew nut shell liquid-derived bisphenol, i.e. 4-(4-hydroxyphenoxy)-3-pentadecylphenol, by nucleophilic substitution reaction with 4-chloronitrobenzene followed by reduction of the formed 4-(4-nitrophenoxy)-1-(4-(4-nitrophenoxy)phenoxy)-2-pentadecylbenzene. Three new polyetherimides containing multiple ether linkages and pendent pentadecyl chains were synthesized by one-step high-temperature solution polycondensation of APPPA in m-cresol with three aromatic dianhydrides, i.e. 3,3,4,4-oxydiphthalic anhydride, 4,4-(hexafluoroisopropylidene)diphthalic anhydride and 3,3,4,4-biphenyltetracarboxylic dianhydride. Inherent viscosities and number-average molecular weights of the polyetherimides were in the ranges 0.66-0.70 dLg(-1) and 17100-29700gmol(-1) (gel permeation chromatography, polystyrene standards), respectively, indicating the formation of reasonably high molecular weight polymers. The polyetherimides were soluble in organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethylsulfoxide, and could be cast into transparent, flexible and tough films from their solutions in chloroform. The polyetherimides exhibited glass transition temperatures (T-g) in the range 113-131 degrees C. The lowering of T-g could be attributed to the combined influence of flexibilizing ether linkages and pentadecyl chains which act as packing-disruptive' groups. The temperature at 10% weight loss (T-10), determined from thermogravimetric analysis in nitrogen atmosphere, was in the range 460-470 degrees C demonstrating good thermal stability. The virtues of solubility and large gap between T-g and T-10 mean that the polyetherimides containing pendent pentadecyl chains have possibilities for both solution as well as melt processability. (c) 2015 Society of Chemical Industry
Keywords: CNSL; ether linkage; pentadecyl; polyetherimide; processability

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.